Technological and food potential of Acrocomia aculeate vegetal beverage (Acta Scientiarum. Health Sciences, 2025)
The study evaluated the physical, chemical, technological and microbiological characteristics of the vegetable drink from A. aculeata, in different proportions of pulp dilution: water (1:10, 1:15 and 1:20 m/m), extraction temperatures (30, 50 and 80ºC), after thermal treatment at 60ºC20min-1 and in natural conditions. Titratable acidity values were below 0.1%, indicating low levels of organic acids. The pH varied close to neutrality (pH 6-8), favoring the non-precipitation of proteins. The soluble solids contents were low, varying from 1 to 2 °Brix before the heat treatment, and from 0.3 to 1.6 after the treatment, with a low °Brix content, which can be explained by the low acidity content, giving a more pleasant taste to the palate. The extraction temperature influenced the technological parameters of color and viscosity, with extractions at 30°C showing more yellowish tones, while those performed at 50 and 80°C had more orange tones. Viscosity increased with increasing temperature, and the results were superior to those found in other studies with vegetable beverages. The microbiological analyzes were carried out in accordance with the microbiological standards recommended by the legislation, and were considered suitable for consumption, indicating that the thermal treatment was efficient to inactivate and reduce the microbiota present in the fruits. Cluster analysis was performed using the dendrogram and principal components (PCA) in order to investigate the association between the combinations of extraction temperature, dilution ratio and undergoing or not through heat treatment. The results obtained show that the extraction temperature factor (30, 50 and 80°C) within the same dilution ratio (1:10, 1:15 and 1:20), did not generate statistically significant difference. We concluded that it was possible to produce an extract of bocaiuva pulp with great technological and nutritional potential, with guaranteed food safety and free from pathogenic microorganisms.